Archetypal Patterns of Leadership in Nurse Managers: A Narrative Inquiry Approach in Clinical Practice - Fitri Nurlina; Usman Sasyari; Mardiana Mochamad Ramdan; Nindya Queena Amelia; Dhiqi Abdul Haq (LP3M Universitas Muhammadiyah Tasikmalaya, 2026)
Background: Nurse managers play a crucial role in shaping the quality of nursing care and organizational culture. However, their leadership characteristics often remain implicit and deeply embedded within personal experiences and professional narratives. Archetypal patterns provide a lens to uncover symbolic dimensions of leadership that influence managerial practices in clinical settings. Objective: This study aimed to investigate the leadership characteristics of nurse managers through archetypal patterns using a narrative inquiry approach in clinical practice. Methods: A qualitative narrative inquiry design was employed. Data were collected from [X] nurse managers working in [hospital/clinical setting] through in-depth interviews, reflective journals, and field observations. Narrative data were analyzed thematically, guided by archetypal frameworks (e.g., caregiver, ruler, warrior, sage), to identify underlying leadership patterns. Results: Findings revealed four dominant archetypal patterns shaping nurse managers’ leadership: the Caregiver (emphasizing compassion and protection), the Ruler (prioritizing structure, authority, and decision-making), the Warrior (focusing on resilience and advocacy), and the Sage (highlighting wisdom and reflective practice). These archetypes manifested differently depending on situational demands, organizational context, and personal values. Conclusion: Nurse managers’ leadership is characterized by dynamic interplay between multiple archetypal patterns. Recognizing these patterns provides new insights into leadership development, mentoring, and strengthening clinical governance. Future research should explore archetypal leadership across diverse healthcare contexts to support transformative nursing leadership.